A Legal Assessment of Biodiversity Conservation Strategies in Cameroon: The Case of Endangered Species (African Journal of Law and Politics, 2025)
Endangered species are the population of organisms which are at high risk of becoming extinct due to ecological factors but most importantly due to the conduct of human activities resulting to loss of habitats, high death rate or changes in environmental conditions/standards. Weak legal framework on the protection of endangered species, environmental degradation due to population pressure on natural resources (such as forests) and laxity in field monitoring and control are some of the factors driving many endangered species in Cameroon to extinction. Without adequate legal protection or conservation measures, endangered species will disappear permanently from the earth surface and consequently depriving future generations from benefiting therefrom. This paper examines the various legal conservation strategies or measures adopted by the government of Cameroon in the protection of biodiversity in general and endangered species in particular. It also reveals the challenges involved in the sustainability of endangered species. In the end, the paper recommends the need for: law-makers to limit referrals to texts of application and legislative cross referencing; capacity building of forest dependent communities; the promotion of cultural practices which favour conservation of natural resources and the use of alternative sources of fuel wood energy among others.